2022
DOI: 10.3390/jcm11040922
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Digital Analysis of Contour Changing after Tooth Extraction with or without Using Less Traumatic Surgical Procedures

Abstract: Background: The present retrospective analysis aimed to compare two different single tooth extraction surgical approaches in both premolar and molar areas: less traumatic magneto-electrical versus conventional tooth extraction in minimizing the edentulous ridge volume loss. Methods: In the present retrospective control trial, 48 patients who underwent one-tooth extraction, were allocated either to control (28 sites treated with conventional tooth extraction procedures) or test group (20 subjects treated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Although atraumatic extraction showed decreased bone loss in ridge width and height of lingual plate of bone than traumatic extraction, perhaps due to the fact that it's a vertical extraction technique which requires no load on the bone plates, and hence no bone resorption later on. These results are in line with the results of Menchini-Fabris et al 2022 18 , as they found no significant differences in height of bone buccally and lingually in atraumatic and traumatic extraction groups although they used 3-dimensional intra-oral scanner instead of CBCT and followed up the patients for 4 months. Considering changes in height of buccal plate of bone, there was a controversy between results of mean of change in bone height and median of the change, this is related to presence of one case of sever bone loss in atraumatic group (Loss of 12.6mm).…”
Section: Bone Formation In Depth Of Extraction Socket (Mm)supporting
confidence: 90%
See 1 more Smart Citation
“…Although atraumatic extraction showed decreased bone loss in ridge width and height of lingual plate of bone than traumatic extraction, perhaps due to the fact that it's a vertical extraction technique which requires no load on the bone plates, and hence no bone resorption later on. These results are in line with the results of Menchini-Fabris et al 2022 18 , as they found no significant differences in height of bone buccally and lingually in atraumatic and traumatic extraction groups although they used 3-dimensional intra-oral scanner instead of CBCT and followed up the patients for 4 months. Considering changes in height of buccal plate of bone, there was a controversy between results of mean of change in bone height and median of the change, this is related to presence of one case of sever bone loss in atraumatic group (Loss of 12.6mm).…”
Section: Bone Formation In Depth Of Extraction Socket (Mm)supporting
confidence: 90%
“…A lot of interventions for conservative extraction were lately introduced to the market trying to decrease this complications such as periotomes 7 , powertome 8 , piezotome 9 , sonosurgery 10 , using endo H file 11 , physics forceps 12,13 , Benex I 14 , Benex II extraction systems 15 , Sapian extraction kit 16 , the use of implant drills 17 and the use of electromagnetic device (Osseotouch) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…All patients showed good healing with low to moderate pain and few complications. This may be due to the new trend of minimally invasive surgery that pushes clinicians to perform flapless extractions and without sutures; plus, the design of the study may have influenced the good results for the reported pain outcomes: only single extractions that did not require antibiotics or corticosteroid therapy in healthy patients were included in the study [ 14 ]. The amino acid and hyaluronic acid-based gel that we tested should enhance the endogenous process of cell reparation and defense, reducing the use of painkillers by patients and reducing the volume changes in the test group, meaning less swelling 1 week after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The root canals were obturated with gutta-percha and root canal sealer. Two months later, the crown of the teeth was separated using a fine needle diamond bur, and the mesial part was extracted atraumatically to better preserve the alveolar crest volume and reduce the loss of external contour [ 9 ]. The remaining crown was restored with composite resin and the patient was scheduled for three months for recovery.…”
Section: Case Presentationsmentioning
confidence: 99%